Post-preload undrained uniaxial capacities of skirted circular foundations in clay. (1st January 2018) - Fu, D.; Gaudin, C.; Tian, Y.; Bienen, B.; Cassidy, M.J.
Abstract: Improvement of the undrained capacities of foundation as a result of preloading, has received attention in offshore engineering only recently. It offers the benefit of optimising foundation design and reducing footprint and cost. This paper investigates the preloading performance of skirted circular foundations in clay using 3D coupled finite-element analyses. The increase in the ultimate undrained uniaxial vertical, horizontal and moment capacities is provided for non-dimensional groups of foundation skirt length, in situ undrained shear strength heterogeneity, magnitude of vertical preload and normalised consolidation time. An exponential relationship between preloading gain in capacity and normalised consolidation time is established, with the maximum preloading gain expressed as a function of the three other dimensionless groups. An approach to estimate the post-preload undrained ultimate uniaxial capacities of skirted circular foundations on normally consolidated clay is ultimately proposed. The influence of foundation geometry is discussed via comparison with the existing solutions. Highlights: Proposing an approach to estimate the post-preload undrained uniaxial capacities of skirted circular foundations. Considering the wide range of foundation skirt length, soil properties, and the loading conditions. Simplified formula to predict the time-related gains in undrained vertical, horizontal and moment capacities. Good agreements by comparing the results obtained from the proposed formula and from the coupled FEA modelling.